PEMBERDAYAAN KADER DALAM PEMANFAATAN RAPOR KEHAMILAN SEBAGAI “SELF ASSESMENT” UNTUK IBU HAMIL - Siska Helina; Juraida Roito Harahap; Septi Indah Permata Sari (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2022)
The Covid pandemic period caused health services to be limited, so WHO recommended online health services and self-assessment of health conditions at home. The aim of this community service is to socialize the Pregnancy “Rapor” Book to Cadres. This Community Service activity was carried out in the Hall of the Umban Sari Public Health Center, Pekanbaru City, for the January-September 2022 period. The participants of this activity were all cadres representing all posyandu in the working area of ​​the Umban Sari Health Center as many as 14 people. The method of activity used in this community service activity is a question and answer lecture, brainstorming, discussion and role playing in filling out the book "Rapor" Pregnancy. The media used was the Pregnancy "Report" Book which was distributed to mothers before the activity started. The evaluation was assessed using a questionnaire sheet with open-ended questions to determine the participants' understanding and an observation sheet to determine the mother's skills. The results obtained are that there are differences in understanding from before community service activities were carried out regarding self-assessment by pregnant women and there are still several variables that have not been completed in filling out the Pregnancy "Report" book. It is recommended to be able to practice using the book "Report of Pregnancy" for pregnant women. Keywords: Empowerment, kader, Rapor Kehamilan